Back to the future. Part III [videorecording (DVD)] - Zemeckis, Robert, 1952-; Fox, Michael J., 1961-; Lloyd, Christopher, 1938-; Steenburgen, Mary (Universal, 2009)
Doc Brown has decided to live in the Old West of the 1880's. But when he's in danger of meeting an untimely end, Marty travels back into the past to rescue him. There's just one problem: Doc is so smitten by a schoolteacher that he's become distracted. Now, it's up to Marty to keep Doc out of trouble, get the DeLorean running, and put the past, present and future on track so they can all get back to where and when they belong.